2002
DOI: 10.1038/nrn755
|View full text |Cite
|
Sign up to set email alerts
|

Control of goal-directed and stimulus-driven attention in the brain

Abstract: We review evidence for partially segregated networks of brain areas that carry out different attentional functions. One system, which includes parts of the intraparietal cortex and superior frontal cortex, is involved in preparing and applying goal-directed (top-down) selection for stimuli and responses. This system is also modulated by the detection of stimuli. The other system, which includes the temporoparietal cortex and inferior frontal cortex, and is largely lateralized to the right hemisphere, is not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

787
8,871
61
63

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10,900 publications
(9,782 citation statements)
references
References 108 publications
787
8,871
61
63
Order By: Relevance
“…Although much attention has been devoted to general visual deficits in ASD (Behrmann, et al, 2006; Dakin and Frith, 2005; Kaiser, et al, 2010), little is known about the involvement of EBA in ASD. The prefrontal cortex (PFC), especially the lateral PFC (LPFC), has been associated with executive control and information integration during socio-emotional processing and is a domain-general area (Corbetta and Shulman, 2002; Levy and Wagner, 2011; Romanski, 2007). Deficits in LPFC responses have been found in individuals with ASD (Kaiser, et al, 2010; Shafritz, et al, 2008; Silk, et al, 2006), supporting the hypothesis that ASD individuals have difficulty in integrating information from different modalities (Happe and Frith, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although much attention has been devoted to general visual deficits in ASD (Behrmann, et al, 2006; Dakin and Frith, 2005; Kaiser, et al, 2010), little is known about the involvement of EBA in ASD. The prefrontal cortex (PFC), especially the lateral PFC (LPFC), has been associated with executive control and information integration during socio-emotional processing and is a domain-general area (Corbetta and Shulman, 2002; Levy and Wagner, 2011; Romanski, 2007). Deficits in LPFC responses have been found in individuals with ASD (Kaiser, et al, 2010; Shafritz, et al, 2008; Silk, et al, 2006), supporting the hypothesis that ASD individuals have difficulty in integrating information from different modalities (Happe and Frith, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Frontoparietal brain regions are recruited when attention is drawn to sensory stimuli [Carlson et al, 1998; Corbetta and Shulman, 2008; Hopfinger et al, 2000; Kastner et al, 1999; Shomstein and Yantis, 2006; Yantis et al, 2002]. Specifically, dorsal frontoparietal activity is increased during tasks that require attentional orienting to visual stimuli and locations [Corbetta et al, 2002]. Several studies have shown the existence of retinotopic maps in both dorsal frontal (frontal eye fields [FEF]) and dorsal parietal regions [superior parietal lobe (SPL); Moore and Armstrong, 2003; Ruff et al, 2008; Saygin and Sereno, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, subjects make visually guided saccades from a central fixation point toward a peripheral target, such as a dot or a geometric shape, in each trial of the prosaccade task (Hallett, 1978; Hutton, 2010), which is a popular paradigm to explore the neural and cognitive mechanisms of eye movements. Previous neuroimaging studies have shown that frontoparietal attentional regions play a critical role in eye movements (Corbetta & Shulman, 2002; Simon, Mangin, Cohen, Le Bihan, & Dehaene, 2002), consistent with their function for spatial representation and spatial updating (Merriam, Genovese, & Colby, 2003; Pertzov, Avidan, & Zohary, 2011; Silver & Kastner, 2009). In a recent meta‐analysis, Jamadar, Fielding, and Egan (2013) have used the activation likelihood estimation method (ALE; Turkeltaub et al., 2012; Eickhoff et al., 2009; Eickhoff, Bzdok, Laird, Kurth, & Fox, 2012) to compare the neural networks of prosaccades and antisaccades.…”
Section: Introductionmentioning
confidence: 82%
“…These findings are basically consistent with the known organization of brain function. The superior part of the PreCG, the FEF, is related to goal‐directed saccades and spatial processing (Corbetta & Shulman, 2002), whereas, the inferior part of the PreCG, the IFG, is related to the identification of objects such as words and faces (McDermott, Buckner, Petersen, Kelley, & Sanders, 1999). While the SPL is related to spatial processing, such as the formation of spatial maps for the control of eye movements (Graziano & Gross, 1998), the IPL serves as an orthography‐phonology transmitter in the word reading and auditory‐motor interface in language processing (Hickok & Poeppel, 2000).…”
Section: Discussionmentioning
confidence: 99%